2020
DOI: 10.1128/mbio.02657-19
|View full text |Cite
|
Sign up to set email alerts
|

Microbiomes Reduce Their Host’s Sensitivity to Interspecific Interactions

Abstract: Bacteria associated with eukaryotic hosts can affect host fitness and trophic interactions between eukaryotes, but the extent to which bacteria influence the eukaryotic species interactions within trophic levels that modulate biodiversity and species coexistence is mostly unknown. Here, we used phytoplankton, which are a classic model for evaluating interactions between species, grown with and without associated bacteria to test whether the bacteria alter the strength and type of species interactions within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 77 publications
0
19
0
Order By: Relevance
“…Moreover, separating interaction networks at the scale of microbial versus 'macrobial' organisms is likely to result in incomplete understanding of the system. Recent work from phytoplankton communities found that the hostassociated bacteria not only changed host growth rate, but also altered the carrying capacity of host populations [58]. Given the importance of carrying capacity and growth rate in shaping competition and community diversity, this finding emphasizes the great need for better integration of host and microbial networks in understanding species' ecologies, and highlights how host-microbiome interactions can drive eco-evolutionary dynamics.…”
Section: The Coevolution Of Host-symbiont Interactionsmentioning
confidence: 88%
“…Moreover, separating interaction networks at the scale of microbial versus 'macrobial' organisms is likely to result in incomplete understanding of the system. Recent work from phytoplankton communities found that the hostassociated bacteria not only changed host growth rate, but also altered the carrying capacity of host populations [58]. Given the importance of carrying capacity and growth rate in shaping competition and community diversity, this finding emphasizes the great need for better integration of host and microbial networks in understanding species' ecologies, and highlights how host-microbiome interactions can drive eco-evolutionary dynamics.…”
Section: The Coevolution Of Host-symbiont Interactionsmentioning
confidence: 88%
“…Climate changes also affect plant ranges and allow some species to expand or narrow their ranges ( Morin, Viner & Chuine, 2008 ). The formation of new interspecific relationships between plant species under climate change may drive these ecological processes ( Little et al, 2016 ), and endophytes may modulate the interspecific interactions and vegetation composition ( Porras-Alfaro & Bayman, 2011 ; Jackrel et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The carbon chain lengths were C6-24. Moreover, the interactions between species are very complex, ranging from cooperation to competition and even predation 33,34 . E. coli can significantly influence candidal growth and induce hyphal death 35 .…”
Section: Discussionmentioning
confidence: 99%